DIGITAL TRANSFORMATIONAL LEADERSHIP OF WILLIAM TANUWIJAYA (FOUNDER OF TOKOPEDIA) - Ardi Ardi; Yohana F. Cahya Palupi Meilani; Veronica Sinaga (Milestone: Journal of Strategic Management, 2023)
Technology and the internet are helping to create new ideas and opportunities by digitizing customers, businesses, products, services, and processes. Businesses can influence every digital area, including consumers, employees, partners, business processes, and a global network of companies and objects. These circumstances result in fundamental adjustments in social behavior and associated repercussions. Organizations require digital transformational leadership to adapt to innovation, creativity, and change capacity. This research aims to explain the idea of digital transformational leadership as a trait of future CEOs of digital businesses. Evidence from the literature suggests that digital transformational leaders enhance organizational innovativeness and performance in many successful businesses. The founder of the Indonesian technology company Tokopedia, William Tanuwijaya, is analyzed using descriptive and phenomenological methodologies for his digital transformational leadership style. As a preliminary study, the research discusses how William's digital transformational leadership philosophy and tactics helped Indonesian market startup Tokopedia prosper.